Rampant chloroplast capture in Sarracenia revealed by plastome phylogeny - Baldwin, Ethan; McNair, Mason; Leebens-Mack, Jim (Frontiers in Plant Science, 2023)
Introgression can produce novel genetic variation in organisms that hybridize. Sympatric species pairs in the carnivorous plant genus Sarracenia L. frequently hybridize, and all known hybrids are fertile. Despite being a desirable system for studying the evolutionary consequences of hybridization, the extent to which introgression occurs in the genus is limited to a few species in only two field sites. Previous phylogenomic analysis of Sarracenia estimated a highly resolved species tree from 199 nuclear genes, but revealed a plastid genome that is highly discordant with the species tree. Such cytonuclear discordance could be caused by chloroplast introgression (i.e. chloroplast capture) or incomplete lineage sorting (ILS). To better understand the extent to which introgression is occurring in Sarracenia, the chloroplast capture and ILS hypotheses were formally evaluated. Plastomes were assembled de-novo from sequencing reads generated from 17 individuals in addition to reads obtained from the previous study. Assemblies of 14 whole plastomes were generated and annotated, and the remaining fragmented assemblies were scaffolded to these whole-plastome assemblies. Coding sequence from 79 homologous genes were aligned and concatenated for maximum-likelihood phylogeny estimation. The plastome tree is extremely discordant with the published species tree. Plastome trees were simulated under the coalescent and tree distance from the species tree was calculated to generate a null distribution of discordance that is expected under ILS alone. A t-test rejected the null hypothesis that ILS could cause the level of discordance seen in the plastome tree, suggesting that chloroplast capture must be invoked to explain the discordance. Due to the extreme level of discordance in the plastome tree, it is likely that chloroplast capture has been common in the evolutionary history of Sarracenia.